Electromagnetic and acoustic coupling during mechanical action in porous media (current status) - Silva, Hugo Gonçalves (2012)
Electromagnetic and acoustic coupling (EAC) during mechanical action, was theoretically predicted to occur in porous media [1] and was recently validated experimentally [2]. In fact, the exchange of acoustic waves to electromagnetic emissions is commonly referred in the literature as seismo-electromagnetic phenomena and is engaging a large number of geophysical groups on its study [3]. The reason for this interest is the observation of peculiar electromagnetic effects in the preparatory stage of impending earthquakes, normally 1 to 10 days before the hazard. Among these we have: 1) abnormal ultra-low-frequency electromagnetic emissions [4]; 2) disturbances in very-low-frequency and low-frequency radio transmissions [5]; 3) atypical infrared emissions [4]; 4) anomalies in the atmospheric electrical field [6]. Obviously, this is a very complex subject since Earth is highly non-uniform in what is related with geomaterials (rocks, water content, etc.) and the comprehension of its fundamental Physics is a great challenge. Thus it prompted diverse perspectives about the SEP mechanisms (to mention a few): 1) electrical charge creation in the vicinity of fracture [7]; 2) microfracturing electrification [8]; 3) electrokinetic effect [1]. Revealing that there is a lot of work to be done in this area. In this context, our project aims to focus on the study of the Physics involved in the EAC during mechanical action. It concerns three aspects: 1) Inspection of the electronic transport process mechanisms occurring in porous media; 2) Measurement of acoustic and electromagnetic emissions under controlled stress or deformation; 3) Theoretical modulation of the possible EAC mechanisms during material fracture. The presentation will give a brief introduction to this interesting area and will focus on the current status of the project. In fact, the recent results obtained in collaboration with the University of Aveiro and the associated laboratory I3N-Aveiro on the electrical characterization of granitic rocks will be discussed. [1] S. Pride, Governing equations for the coupled electromagnetics and acoustics of porous media, Phys. Rev. B 50, 15678 (1994). [2] C. Bordes, L. Jouniaux, S. Garambois, M. Dietrich, J.P. Pozzi, and S. Gaffet, Evidence of the theoretically predicted seismo-magnetic conversion, Geophys. J. Int. 174, 489 (2008). [3] H.G. Silva, M. Bezzeghoud, J.P. Rocha, P.F. Biagi, M. Tlemçani, R.N. Rosa, M.A. Salgueiro da Silva, J.F. Borges, B. Caldeira, A.H. Reis, and M. Manso, Seismo-electromagnetic phenomena in the western part of the Eurasia-Nubia plate boundary, Nat. Hazards Earth Syst. Sci. 11, 241 (2011). [4] T. Bleier, C. Dunson, M. Maniscalco, N. Bryant, R. Bambery, and F. Freund, Investigation of ULF magnetic pulsations, air conductivity changes, and infra red signatures associated with the 30 October Alum Rock M5.4 earthquake, Nat. Hazards Earth Syst. Sci. 9, 585 (2009). [5] P. F. Biagi, L. Castellana, T. Maggipinto, D. Loiacono, L. Schiavulli, T. Ligonzo, M. Fiore, E. Suciu, and A. Ermini, A pre seismic radio anomaly revealed in the area where the Abruzzo earthquake (M=6.3) occurred on 6 April 2009, Nat. Hazards Earth Syst. Sci. 9, 1551 (2009). [6] H.G. Silva, M. Bezzeghoud, A.H. Reis, R.N. Rosa, M. Tlemçani, A.A. Araújo, C. C. Serrano, J.F. Borges, B. Caldeira, and P.F. Biagi, Atmospheric electrical field suppression in the time of the M=4.1 Sousel earthquake (Portugal), Nat. Hazards Earth Syst. Sci. (in press). [7] F. T. Freund, A. Takeuchi, and B. W. Lau, Electric currents streaming out of stressed igneous rocks - A step towards understanding pre-earthquake low frequency EM emissions, Phys. Chem. Earth 31, 389 (2006). [8] O.A. Molchanov and M. Hayakawa, Generation of ULF electromagnetic emissions by microfaturing, Geophys. Res. Lett. 22, 3091 (1995).